Socioeconomic Outcomes as Determinants of Pathao Riders’ Welfare in the Platform Economy - Poudel, Shankar Nath; Baral, Indrakala (Asian Journal of Population Sciences, 2026)
The swift expansion of ride-sharing services has changed urban mobility and employment trends by providing commuters with convenience and riders with flexible earning options in Kathmandu. Pathao riders, however, deal with a number of difficulties, such as health hazards, erratic income, long workdays, and no social protection. This study looks into the socioeconomic factors that affect the welfare of Pathao passengers. A survey-based research design was used to gather data from 150 riders in 15 different sites using Likert-scale questionnaires. The results reveal that riders significantly improve urban mobility because the majority of respondents believe Pathao services are quicker and more convenient to use than traditional modes of transportation. Meanwhile, riders' physical and mental health suffers somewhat, and their income is frequently insufficient to pay for living needs. Many participants engage as part-time workers or have Pathao as an extra source of income, and they are moderately satisfied with whatever they earn, revealing the variety of their individual experiences. So, the study brings out a relationship among financial circumstances, employment contracts, and riders' well-being, showing the need for policy measures to improve job stability, social safety, and common well-being in Nepal's developing platform economy.